Comparison of different estimators of SARS-CoV-2 pandemic activity on geographical and temporal levels - Valter, Remi; Sembajwe, Grace; Descatha, Alexis; Fadel, Marc (Frontiers in Public Health, 2022)
Background Studies began investigating occupational exposures as a source of contamination to SARS-CoV-2, yet few considered the variation in SARS-Cov2 pandemic activity for these exposures. Several indicators were built to assess SARS-Cov2 activity though they usually serve a specific purpose and have limitations. The aim was to compare qualitatively different estimators of the SARS-CoV-2 pandemic activity and to create an estimator of pandemic activity level based on daily hospital admissions for job-exposure matrices (JEM) usage. Methods From publicly available French databases, we retrieved all data from March 19, 2020 (first day available) to March 25, 2021 (day of data collection) on four different estimators: percentage of intensive care bed occupied, reproductive number, tests' positive rate and number positive tests. An indicator based on new daily hospital admissions was created for a COVID JEM. Due to the heterogeneity of the estimators, a qualitative comparison was carried out. Results During the study period, three major outbreaks took place. Though the number of positive tests was the first indicator to worsen during the 2nd outbreak, it failed to identify variation during the outbreak. Though each indicators behaved differently during the study period, the indicator based on new daily hospital admissions and the positive rate seemed to be the closest to one another. Conclusion This study highlights the heterogeneity of the indicators used during the first and second SARS-Cov2 outbreaks in France. An indicator based on new daily hospital admissions seems to be a good candidate for estimating SARS-CoV-2 epidemic activity for COVID JEMs and is easily available in countries where usual indicators are not commonly accessible.